Webmaster enhance skill for e-government websites in compliance with Provider Based Evaluation (ProBE) standard / Azlin Ramli - Ramli, Azlin (2017)
This study focuses and identify the skills and competency of webmaster in government sector using a Digital Government Competency & Capability Readiness (DGCCR) conceptual framework. DGCCR initiative Information System (IS) to upgrade the capabilities and competencies of civil servants to operate in the digital work environment. For evaluation Government Portal Assessment is using Provider-Based Evaluation (ProBE). Provider-Based Evaluation (ProBE) was introduced in 2014 to replace Malaysia Government Portals & Websites Assessment (MGPWA) to ensure the quality portal and meet government standards. Probe criteria set taking into account the characteristics of Government Online Service (GOS) at international level. However, agencies are given the opportunity to assess portal and web site for self-assessment, the provision of services provided to customers for Inside-Out and services that meet the needs of the people (citizen-centricity). Hon. Tan Sri KSN in FCC 39th Meeting dated 2 April 2015, has decided to develop a curriculum INT AN to improve the skills of the webmaster and content portal so that more people-friendly agency (citizen -centric). Aiming to improve the ranking Online Service Index (OSI) Malaysia in the UN EGovernment Survey globally. With this findings, can plan a training road map for webmaster and government staff to sharpen their skill that related with ProBE and MUSE criteria. Webmaster also can fulfill the expectation from the top management.